2008
DOI: 10.1111/j.1365-2648.2008.04768.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing emotion work and interprofessional collaboration in general internal medicine wards: a qualitative study

Abstract: Longstanding emotion work issues must be addressed before nurses will engage collaboratively. We suggest improving nursing collaboration through the refining of holistic nursing information, and reflections on practice by all interprofessional team members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 68 publications
2
99
0
3
Order By: Relevance
“…Indeed, studies have revealed that interprofessional tensions often exist in hallways and corridors of hospitals (e.g. Miller et al, 2008). We argue that hospital design can have an influence on the patterns of interactions between the health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have revealed that interprofessional tensions often exist in hallways and corridors of hospitals (e.g. Miller et al, 2008). We argue that hospital design can have an influence on the patterns of interactions between the health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hugman [26] has noted that professionals may experience multiprofessionalism as a threat to their own professionalism. Therefore, collaboration should be based more on knowledge and competence than on titles [27]. Interaction is needed where it is possible to bring knowledge and different viewpoints together.…”
Section: Discussionmentioning
confidence: 99%
“…Corridor conversations are short opportune interactions used to quickly convey knowledge on patient matters or medical directives as practitioners pass one another in the hallway during routine care, between meetings, or on their way to break. These encounters have been described as being an integral part of hospital life (Long et al, 2007) often fostering interprofessional collaboration on patient care (Oandasan et al, 2009;Reeves, Lewin, Espin, & Zwarenstein, 2010) as well as informal social dynamics among professionals (Miller et al, 2008;Payne et al, 2000;Reeves et al, 2009). Not only can corridors provide opportunities for unplanned communication between professionals but they are also deliberately deployed through the use of loudspeakers and poster and picture boards to communicate intra-and interprofessional staff acknowledgments, admonishments, and disputes Miller et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Emotion work (Miller et al, 2008) or emotional labor is understood as an organizationally sanctioned set of display rules between employees and customers (Hochschild, 1983), or between health care practitioners and patients (McClure & Murphy, 2007). These display rules influence the range of emotional control or expression permitted to maintain an emotional interaction considered appropriate to that particular occupation or incident.…”
Section: From Physical Work To Emotion Workmentioning
confidence: 99%
See 1 more Smart Citation